2015
DOI: 10.1097/igc.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes of Radical Trachelectomy in Early-Stage Cervical Cancer

Abstract: The study shows the feasibility of LRT, with the advantage of reduced blood loss. The LRT could be an alternative option for patients with large tumors. Further researches are needed to investigate the long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Minimally Invasive RT (Pure or Robot-assisted Laparoscopic RT) Two techniques are available: pure laparoscopic (nine series) and robot-assisted laparoscopic surgery (two series, one of which reported the results of both techniques) (Table 4). The first pure laparoscopic procedure was reported in 2002 and the first robot-assisted laparoscopic procedure in 2008 (Table 4) (35,41,86,97,(100)(101)(102)(103)(104)(105)(106)(107)(108)(109). The fertility results of 314 cases were reported.…”
Section: Laparotomic Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally Invasive RT (Pure or Robot-assisted Laparoscopic RT) Two techniques are available: pure laparoscopic (nine series) and robot-assisted laparoscopic surgery (two series, one of which reported the results of both techniques) (Table 4). The first pure laparoscopic procedure was reported in 2002 and the first robot-assisted laparoscopic procedure in 2008 (Table 4) (35,41,86,97,(100)(101)(102)(103)(104)(105)(106)(107)(108)(109). The fertility results of 314 cases were reported.…”
Section: Laparotomic Rtmentioning
confidence: 99%
“…Because it is the first infertility factor, the infertility management most frequently used was cervical dilatation combined or not with IUI or IVF (or both), which yielded good results (9,41). Other specific IVF strategies were published as case reports, particularly in the case of persistent severe stenosis (120)(121)(122)(123).…”
Section: Fertility and Infertilitymentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines suggest that trachelectomy may be a reasonable fertility-sparing treatment option for stage IA and IB1 (tumor size ≤ 2 cm) cervical cancer (Reid et al, 2018). Nonetheless, some clinicians thought that LRT and ART, with more radical parametria resection, is oncologically safe for patients with stage IB1 and a large tumor size (2–4 cm) (Matsuo et al, 2018; Yoon et al, 2015). Moreover, recent study showed a gradual increase in the utilization of trachelectomy for patients with stage IB1 cervical cancer with tumors ≥ 2 cm in the United States (Matsuo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 2,700 cases have been published and more than 900 deliveries have been reported [6]. The feasibility of RT with vaginal, abdominal, laparoscopic and robotic technique have been proven with similar oncologic outcomes [7891011]. However, few prospective data are available on the postoperative morbidity after RT and their consequences on oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%